1995
DOI: 10.2527/1995.73102959x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for litter size in Canadian Yorkshire and Landrace swine with each parity of farrowing treated as a different trait.

Abstract: Genetic variances and covariances for the number of pigs born in total (NOBT), the number of pigs born alive (NOBA), and the number of weaned pigs (NOW) were estimated by REML under an animal model. Data on 30,357 and 42,041 litters born between 1977 and 1992 from Yorkshire and Landrace sows, respectively, were obtained from the Quebec Record of Performance sow productivity program. Data of the first four parities of litter size were used for four different analyses under an animal model: univariate analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
103
3
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 25 publications
23
103
3
5
Order By: Relevance
“…Low genetic correlations between litter size in different parities indicates that phenotype records from different parities should be treated as different traits (Irgang et al, 1994;Roehe & Kennedy, 1995). Direct additive genetic correlations obtained with MT analysis for six traits are lower than in Hanenberg et al (2001), who reported an increase from 0.79 between the first and the second parity to 0.96 between the fifth and the sixth parity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Low genetic correlations between litter size in different parities indicates that phenotype records from different parities should be treated as different traits (Irgang et al, 1994;Roehe & Kennedy, 1995). Direct additive genetic correlations obtained with MT analysis for six traits are lower than in Hanenberg et al (2001), who reported an increase from 0.79 between the first and the second parity to 0.96 between the fifth and the sixth parity.…”
Section: Discussionmentioning
confidence: 89%
“…Knowledge of genetic parameters for litter size in pigs is necessary to estimate accurate breeding values, to optimize breeding schemes, and to predict response to selection (Roehe & Kennedy, 1995). There are several approaches regarding the method for genetic evaluation of litter size.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those found in the present study. However, Roehe & Kennedy (1995) and Holm et al (2005) reported heritability estimates for number of piglets born of about 0.10 when using a model that only included first parity records of Landrace pigs.…”
Section: Resultsmentioning
confidence: 99%
“…These variations are due to the number and quality of the records and the models and estimation methods used. Additionally, there are some controversies in the literature as to whether litter size in different parities should be considered as repeated measurements of the same trait (Southwood & Kennedy, 1990;See et al, 1993;Crump et al, 1997;Lourenço et al, 2008) or as different traits (Irgang et al, 1994;Roehe & Kennedy, 1995;Rydhmer et al, 1995;Barbosa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation